2220. Trends in Follow-up Testing among Patients Positive for Chlamydia and Gonorrhea in the Veterans Health Administration (VHA), 2013-2019. (15th December 2022) - Schirmer, Patricia; Sharma, Aditya; Lucero-Obusan, Cynthia A; Oda, Gina; Holodniy, Mark
Abstract: Background: Chlamydia (CT) and gonorrhea (GC) infections are an ongoing public health issue. CDC recommends testing patients with CT/GC for other sexually transmitted illnesses (STIs) and repeating CT/GC testing 3-12 months later. We described repeat testing and testing for other STIs among GC/CT cases in VHA. Methods: Molecular laboratory testing for CT/GC during 1/1/2013-12/31/2020 was retrieved from VHA data sources. Patients were evaluated for syphilis, HIV, and repeat CT/GC testing within one year after a positive GC or CT test. Differences in characteristics of CT/GC positive patients associated with receiving recommended testing were assessed using the chi-squared test. Results: 41, 630 of 1, 005, 762 (4.1%) CT results (36, 138 unique patients) and 17, 649 of 1, 013, 198 (1.7%) GC results (14, 598 unique patients) were positive; mean age of positive CT/GC patients were 31.5 and 40yo respectively with the largest percentage of cases in the 25-34yo group. Repeat testing within 91-365 days after a positive result were 32.6% and 34.5% for CT and GC, respectively (Table 1-2). Of CT/GC positives receiving repeat testing, 9% of CT and 15% of GC were again positive. HIV testing was performed for 72.4% and 65.5% CT and GC first positives, respectively, while syphilis testing was completed for 66.5% and 60.5% CT and GC, respectively (Table 3-4). In CT and GC patients tested for other STIs, HIV was positive in 2.1% and 5.9%, and syphilis was positive in 4.1% and 11.3%, respectively. Compared to 25-34yo patients with CT or GC, those < 25 had higher odds of inappropriate repeat testing (i.e., retested < 91 days, or not retested within 365 days after positive) but had lower odds of not being tested for HIV and syphilis. CT/GC positive females had lower odds of not being tested for HIV and syphilis. Conclusion: In VHA, nearly 2/3rds CT/GC patients had inappropriate repeat testing, nearly 1/3rd were not tested for HIV/syphilis and up to 15% remained positive for CT/GC, suggesting testing practices and treatment could be improved to better align with current CDC recommendations. STIs not identified and treated appropriately can have serious individual and public health consequences. VHA providers may benefit from additional education on CDC recommended STI guidelines. Disclosures: All Authors : No reported disclosures.